Consumer Experience and Loyalty in the Metaverse: A Systematic Review - Arie Bowo, Ferdian; Rahman Rahim, Abdul; Nut, Nut (Jurnal Manajemen, Akuntansi, Ekonomi, 2025)
This study synthesizes eight articles through a systematic literature review and meta-synthesis to explore consumer experiences in the metaverse and their influence on brand loyalty. Six key themes were identified: Immersion–Presence–Awe Pathway, Avatar and Personalization, Visual Cognition and Decision-Making, Social Presence and Community Identity, Brand Anthropomorphism and Loyalty, and Habituation and Experience Dynamics. Findings show that technological factors such as immersion, avatars, personalization, and visual design act as stimuli that trigger cognitive and emotional responses, including presence, awe, and brand love, shaping engagement, purchase intentions, and loyalty. The study highlights the complex interaction of cognitive, affective, and conative dimensions in immersive environments and underscores the importance for marketers to create interactive, personalized, and sustainable experiences that sustain long-term consumer engagement.